Liver Myofibroblasts - Jiri Kanta (Frontiers Research Topics, 2016)
Myofibroblasts (MFB) are found in most tissues of the body. They have the matrix-producing functions of fibroblasts and contractile properties that are known from smooth muscle cells. Fundamental work of the last decades has shed remarkable light on their origin, biological functions and role in disease. During hepatic injury, they fulfill manifold functions in connective tissue remodeling and wound healing, but overshooting activity of MFB on the other side induces fibrosis and cirrhosis. The present e-book "Liver myofibroblasts" contains 9 articles providing comprehensive information on "hot topics" of MFB. In our opening editorial we provide a short overview of the origin of MFB and their relevance in extracellular matrix formation which is the hallmark of hepatic fibrosis. Thereafter, leading experts in the field share their current perspectives on special topics of (i) MFB in development and disease, ii) their role in hepatic fibrogenesis, and (iii) promising therapies and targets that are suitable to interfere with hepatic fibrosis.